HOMEFOOD randomised trial – Six-month nutrition therapy improves quality of life, self-rated health, cognitive function, and depression in older adults after hospital discharge. (April 2022) - Blondal, B.S.; Geirsdottir, O.G.; Halldorsson, T.I.; Beck, A.M.; Jonsson, P.V.; Ramel, A.
Summary: Background and aims: Malnutrition is common among older adults and is related to quality of life, cognitive function, and depression. To what extent nutrition interventions can improve these outcomes remains unclear. The aim of this study was to investigate the effect of nutrition therapy on health-related quality of life (EQ-5D), self-rated health, cognitive function, and depression in community dwelling older adults recently discharged from hospital. Methods: Participants (>65 years) were randomised into an intervention (n = 53) and a control group (n = 53). The intervention group received individualised nutrition therapy based on the nutrition care process including 5 home visits and 3 phone calls, in combination with freely delivered energy- and protein-rich foods and oral nutrition supplements for six months after hospital discharge. EQ-5D, self-rated health, Mini-Mental-State-Examination (MMSE), and the Centre for Epidemiologic Studies Depression – IOWA (CES-D) scale were measured at baseline and at endpoint. Results: Two subjects dropped out, one from each arm. The control group experienced an increase in depressive symptoms and a decrease in self-rated health during the study period, while the intervention group experienced increases in cognitive function, self-rated health, and EQ-5D resulting in significant endpoint differences between the groups: EQ-5D (0.102, P = 0.001); self-rated health: 15.876 (P < 0.001); MMSE: 1.701 (P < 0.001); depressive symptoms: - 3.072 (P < 0.001); all in favour of the intervention group. Improvements during the intervention in MMSE, self-rated health, and CES-D were significantly related to body weight gain in a linear way. Conclusion: Cognitive function and mental well-being worsen or stagnate in older adults who receive standard care after hospital discharge. However, a six-month nutrition therapy improves these outcomes leading to statistically and clinically significant endpoint differences between the groups. As improvements were related to body weight gain after hospital discharge, we conclude that the increase in dietary intake, with focus on energy and protein density, and changes in body weight might have contributed to better cognitive function and mental well-being in older adults after the intervention.